Other immigrants : the global origins of the American people - Reimers, David M. (New York University Press, 2005)
Publisher description: In Other immigrants, David M. Reimers offers the first comprehensive account of non-European immigration, chronicling the compelling and diverse stories of frequently overlooked Americans. Reimers traces the early history of Black, Hispanic, and Asian immigrants from the fifteenth century through World War II, when racial hostility led to the virtual exclusion of Asians and aggression towards Blacks and Hispanics. He also describes the modern state of immigration to the U.S., where Blacks, Hispanics, and Asians made up nearly thirty percent of the population at the turn of the twenty-first century.